The Application of Safety Education in Primary School Directorate in Indonesia - Evi Widowati; Herry Koesyanto; Sugiharto Sugiharto (Journal of Education and Learning (EduLearn), 2018)
Primary school children are included in the vulnerable group because they are still in a growth and development phase. In Indonesia, many accidents involve children due to their lack of knowledge, excessive energy, and high curiosity. Therefore, it is important to evaluate the application of safety values in formal education material, in order to evaluate how adequate the current teaching materials in encouraging children to practice safety culture.Petompon 2, one of the primary school used in this study, showed that 60% subjects in grade 1 contain application of safety values, and subjects from grade 2 to 6 showed that 14.3%, 90%, 100%, 87.5%, and 50% subjects, consecutively, already contain safety education.The solutions offered are improving teacher’s capacity in learning process and integrating the safety values into education subjects, such as: in sport education, natural science, social science, citizenship education, Islamic religion, mathematics, and Indonesian language. Other methods available are integrating safety values into extracurricular activities and introducing educative game on safety values to primary school students.